Note on distribution of Alysicarpus longifolius (Rottl. ex Spreng.) Wight & Arn. var. major Pokle in India. - Chavan, Shantanu Y.; Taur, Rupali; Ingle, Priya (Plantae Scientia, 2019)
The genus Alysicarpus Desv. is concentrated in India and distributed mostly in the dry zones of the country. During the course of investigation, the authors came across the several specimens Alysicarpus longifolius (Rottl. ex Spreng.) Wight & Arn.var. major Pokle. A. longifolius (Rottl. ex Spreng.) Wight & Arn.var. major Pokle, an endemic taxa, was so far known only from single collection. In the recent survey, numbers of additional populations were found in Central India in addition to the type locality. Extended geographical distribution with illustration has been reported in the present article.